Into the volcano : a graphic novel - Wood, Don, 1945- (Blue Sky Press, 2008)
While their parents are away doing research, brothers Duffy and Sumo Pugg go with their cousin, Mister Come-and-Go, to Kokalaha Island, where they meet Aunt Lulu and become trapped in an erupting volcano.